Power Wheeling Hybrid System of PV-Pumped Storage Using MW-KM Method - Hasana, Frida; Hadi, Sasongko Pramono; Setyonegoro, M. Isnaeni Bambang; Tumiran, Tumiran (2022)
It is widely recognized that using conventional power plants requires an expensive and massive fossil fuel supply. This can be minimized by doing a hybrid conventional power plants and renewable energy sources (RES), along with pumped storage. In this paper, the optimal scheduling of that hybrid system is simulated using MATPOWER Optimal Scheduling Tool (MOST) to obtained the most optimal and economic condition. Utilize the scheduling outcomes and the assumption that power wheeling is implemented, this paper calculates the network lease. This paper provides the leasing calculation using MW-km method with the reverse, absolute, and dominant approach by considering the direction of power flow. According to the simulation results, a scheduling method that includes pumped storage and RES can reduce conventional plant operations. Moreover, this paper shows that the reverse approach produced the lowest calculation results compared to the other approaches. © 2022 IEEE.